Perpendicular drill bit alignment provides a practical guidance to determine the appropriate suture anchor insertion angle during acetabular labral repair. Issue 2 (24th August 2021) - Ismailoglu, Abdul Veli; Ozdogmus, Omer; Karaman, Muhammed Ilkay; Kayaalp, Asim; Kocaoglu, Baris
ABSTRACT: The safe acetabular rim angle is an anatomical measurement used to determine the safety margin when inserting suture anchors. The purpose of the present study was to find out whether aligning the drill bit perpendicularly during arthroscopic surgery can provide a reference point for determining an appropriate angle to facilitate the suture anchor insertion and to prevent extra- and intra-articular perforations. One hundred computed tomographic hips were used to reconstruct three-dimensional acetabular hip models. Each model was radially sectioned at the 4 o'clock, 3 o'clock and anterior inferior iliac spine (AIIS) positions (that corresponded mainly to the 2:20 clock position). A perpendicular reference line, representing a perpendicular drill bit alignment, was drawn for each position within the acetabular model, and its relation to the safe acetabular rim angle was measured. The length of the perpendicular reference line and the effect of gender on measurements were also evaluated. The mean safe acetabular rim angle at the 3 o'clock position was significantly smaller compared to other clock positions ( P < 0.001). The perpendicular reference line was located out of the safe acetabular rim angle in 28 cases (%28), mostly in female acetabula at the 3 o'clock position, and relative to the perpendicular reference line the required minimal angle was 4° ± 2.3° to place the anchor in the safe acetabular rim angle to avoid extra-articular perforation. The perpendicular reference line was shortest at the 3 o'clock position, and its mean length was shorter in female acetabula at all clock positions ( P < 0.001). Aligning the drill bit perpendicular to the acetabular opening plane during an arthroscopic anchor placement is a practical way to estimate and target the position of the safe acetabular rim angle to avoid anchor perforations. Based on measurements from a perpendicularly aligned drill bit, the drill bit should be directed towards the joint minimally by 4° to avoid extra-articular perforations and maximally by 30° to avoid intra-articular perforations.